The influence of type 2 diabetes and its metabolic correlates in middle-aged adults on cognition at mid and later life; A systematic review and meta-analysis - Oisin C. Joyce; Cliodhna McHugh; David Mocker; Fiona Wilson; Áine M. Kelly (PLoS ONE, 2025)
Introduction While previous studies have examined the link between Type 2 Diabetes Mellitus (T2DM) and cognitive function in middle-aged adults, no review has explored the long-term effects on cognition of T2DM when diagnosed at midlife. This review aims to investigate any association between T2DM and its metabolic correlates during midlife and measures of cognitive function, spanning from midlife into later life. Methods Electronic databases (EMBASE, Medline, CINAHL, Web of Science) were explored from their establishment until December 2023 to identify studies exploring the link between T2DM in midlife (40–65 years) and cognitive function. T2DM was defined based on ESC and AHA criteria, encompassing diabetes status, FBG, HbA1c levels, and MetS presence. Cognitive function in mid and/or later life was categorised into functioning sub-domains, with tests selected to reflect predominant cognitive functions utilised. A random-effects meta-analysis was performed, and study quality assessed using the AXIS tool. Results We included 151 studies of moderate to high quality. Studies were independently screened in a step-by-step process, with a subset of studies that met the criteria selected for inclusion in a meta-analysis. Due to limited availability of raw data for cognitive measures at later life, meta-analysis was conducted on studies assessing cognitive function at midlife only. In the case of later life, the majority of longitudinal studies reported negative relationships between midlife T2DM and cognitive function, specifically in the modalities of executive function and global cognition; findings for memory were conflicting. Qualitive assessment of 107 studies where cognitive function was assessed at midlife found no association between it and midlife T2DM. However, meta-analysis of 10 studies revealed a negative impact of T2DM on memory (MD = −0.19; 95% CI = −0.26 to −0.11; I2 = 25%), executive function (MD = −0.14; 95% CI = −0.25 to −0.04; I2 = 0%), and global cognition (MD = −0.26; 95% CI = −0.34 to −0.17; I2 = 0%). Discussion This study highlights the impact of midlife T2DM on a variety of cognitive domains from midlife onwards, suggesting that timely diagnosis of T2DM and its careful management may be an important strategy in preserving cognitive function through the lifespan. Given the contrast in results from qualitative and quantitative analysis that we report in the case of midlife cognitive function, we also emphasise the value of combining both methodological approaches where possible.